Acrosomal Changes during Liquid Preservation of Boar Semen with BTS, KLEV and BI-1 Dilutors - PANDEY, R P; SINGH, B K (The Indian Journal of Animal Reproduction, 2023)
Changes in acrosome morphology of 12 semen samples diluted with BTS, Kiev and 81-1dilutors and preserved for 0, 24, 48 and 72 hours were evaluated. Highly significant (P
Keywords: Acrosomal Changes; Boar Semen; BTS; KLEV